Alternative means of access to circulation for chronic haemodialysis. Issue 5979 (9th August 1975) - Gordon, E M
Abstract : Various standard techniques of access to the circulation for haemodialysis are ideal for most patients. Another type of internal fistual of large vessels, between the saphenous vein and the femoral artery, has been found useful in patients whose peripheral vessels are unsuitable for the standard means of access.